2009
DOI: 10.1111/j.1750-3841.2009.01161.x
|View full text |Cite
|
Sign up to set email alerts
|

Seed Viability and Functional Properties of Broccoli Sprouts during Germination and Postharvest Storage as Affected by Irradiation of Seeds

Abstract: The viability of broccoli seeds and functional properties, such as ascorbic acid, carotenoid, chlorophyll, and total phenol contents, of broccoli sprouts grown from irradiated seeds were evaluated. The seeds were irradiated using electron beam and gamma ray at doses up to 8 kGy. High germination percentages (>90%) were observed in seeds irradiated at < or =4 kGy, but the yield ratio and sprout length decreased with increased irradiation dose. Irradiation at > or =6 kGy resulted in curling of the sprout roots. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Irradiation reduced the germination of the Chinese cabbage seeds, which resulted in underdeveloped sprouts with lower carotenoid contents compared with those grown from the nonirradiated ones (Waje et al . 2009a). However, all sprouts were found with a significantly higher carotenoid content during storage with overall better values for the sprouts from the nonirradiated seeds.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Irradiation reduced the germination of the Chinese cabbage seeds, which resulted in underdeveloped sprouts with lower carotenoid contents compared with those grown from the nonirradiated ones (Waje et al . 2009a). However, all sprouts were found with a significantly higher carotenoid content during storage with overall better values for the sprouts from the nonirradiated seeds.…”
Section: Resultsmentioning
confidence: 99%
“…2009c), broccoli (Waje et al . 2009a) and alfalfa (Randhir et al . ) seeds with variable responses in their germination and nutritional properties on irradiation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there was no difference in the relative growth percentage of plantlets irradiated with either electron beam or gamma irradiation with similar doses. Waje et al (2009) showed that broccoli seeds irradiated with the same dose of either electron beam or gamma rays had similar germination percentages. They also reported a decrease in sprout length of germinated seedlings with increase in dose of either gamma ray or electron beam.…”
Section: Effects Of Gamma and Electron Beam Irradiation On The Growthmentioning
confidence: 95%
“…Irradiation treatment has been studied on a wide variety of seeds and D 10-values for various pathogens have been calculated for use in designing treatments to meet the FDA requirement for seed decontamination methods to achieve >5-log reduction (134,176,177). A radiation dose of 5.9 kGy has been recommended to achieve a 5-log reduction on broccoli and radish sprouts (176).…”
Section: Physical Interventions: Thermal Inactivationmentioning
confidence: 99%